Exploring the intramolecular catalysis of the proton exchange process to modulate the relaxivity of Gd(iii)-complexes of HP-DO3A-like ligands. Issue 72 (22nd August 2018) - Carnovale, Irene Maria; Lolli, Marco Lucio; Serra, Sonia Colombo; Mingo, Alberto Fringuello; Napolitano, Roberta; Boi, Valeria; Guidolin, Nicol; Lattuada, Luciano; Tedoldi, Fabio; Baranyai, Zsolt; Aime, Silvio
Abstract : The Gd III complex of Ph-HP-DO3A shows the highest contribution to the relaxivity by the intramolecular proton exchange of the –OH group. Abstract : The Gd(iii )-complexes of three novel HP-DO3A-like ligands have been investigated to assess the relationship between relaxometry and intramolecular catalysis of the proton exchange. The structures of these ligands differ from the parent HP-DO3A because the methyl group of the hydroxy-propyl arm has been replaced by –Ph–OH, –Ph–NH2 and –Ph–COOH, respectively. The phenol, amine and carboxylate functionalities display an intramolecular H-bonding with the coordinated hydroxyl moiety that affects either the p K values of the involved functionalities and the rate of the proton exchange process.